2015
DOI: 10.1111/cup.12515
|View full text |Cite
|
Sign up to set email alerts
|

Intravascular NK/T‐cell lymphoma: a report of five cases with cutaneous manifestation from China

Abstract: Intravascular NK/T-cell lymphoma is a rare highly aggressive and EBV-associated lymphoma that is prone to develop in Chinese patients. The relationship between intravascular NK/T-cell lymphoma and extranodal NK/T-cell lymphoma, nasal type, requires clarification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 37 publications
0
17
0
Order By: Relevance
“…In our cohort, 2 Caucasian patients (7.7%) presented “Asian variant” IVL; this observation is not unusual, as cases of “classical” IVL have been reported in Asians and “Asian variant” IVL has been reported in Europeans and Africans. [ 3 , 39 – 44 ] This leads us to believe that IVL nomenclature should use “classical IVL” and “IVL associated with hemophagocytic syndrome,” instead of “European IVL” and “Asian variant” IVL.…”
Section: Discussionmentioning
confidence: 99%
“…In our cohort, 2 Caucasian patients (7.7%) presented “Asian variant” IVL; this observation is not unusual, as cases of “classical” IVL have been reported in Asians and “Asian variant” IVL has been reported in Europeans and Africans. [ 3 , 39 – 44 ] This leads us to believe that IVL nomenclature should use “classical IVL” and “IVL associated with hemophagocytic syndrome,” instead of “European IVL” and “Asian variant” IVL.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al [ 13 ] reported 5 cases of NK/T-cell IVL, but, as commented by Alegria-Landa et al [ 8 ] in 2017, the possibility of an extranodal NK/T-cell lymphoma nasal-type in their case number 2 cannot be excluded. As well in their case number 5, the presence of circulating atypical CD56 positive lymphocytes, makes aggressive NK leukemia the most likely diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…NK/T-cell IVL often follows an aggressive clinical course, however, the prognosis may vary with the extent of disease, being more favorable in patients with exclusive skin lesions. In particular 2 cases with the disease limited to the skin had a really favorable outcome, being in complete remission after 1.5 and 3 years [ 13 , 15 ]. However, the limited number of cases makes difficult to draw any conclusion.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth remembering that CD30 could be expressed by any type of EBV-related lymphoproliferative disease and, in fact, it was positive in our case and in four other published cases of NK/T IVLs. 13,22,28,29 A few cases of primary cutaneous anaplastic CD30 + T cell lymphoma with exclusive intravascular localization have also been described. [35][36][37][38] However, in contrast with NK/T IVLs, in cutaneous anaplastic CD30 + IVLs neoplastic cells are confined within the D2-40-positive dermal lymphatic vessels, EBER-1 is negative and the course of this cutaneous anaplastic CD30 + IVL is mainly indolent.…”
Section: Discussionmentioning
confidence: 99%